2016
DOI: 10.1039/c6ra08706j
|View full text |Cite
|
Sign up to set email alerts
|

Effect of temperature and alloying elements (Fe and Bi) on the electrical resistivity of Sn–0.7Cu solder alloy

Abstract: In this paper, we investigated the electrical resistivity as a function of temperature of the Sn-0.7Cu solder alloy with the addition of Fe and Bi. The electrical resistivity were characterized by the four-point probe method. Apparent change in electrical resistivity was witnessed by the addition of both Fe and Bi. At room temperature, the electrical resistivity was found to be increased with the addition of Fe, as well as a further increase with the addition of Bi. Fe and Bi modified Sn-0.7Cu alloys also expe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(7 citation statements)
references
References 37 publications
(35 reference statements)
0
5
0
Order By: Relevance
“…204−206 The effect of the alloying element was related to the size mismatch, where alloying atoms with atom radii 15% or larger than the pure metal lead to a grave effect on the electrical conductivity, to a higher degree of disorder in the structure, and to weaker interatomic interactions. 78,204,206 A similar effect of alloying can be observed for the liquid metals EGaIn and Galinstan, which show lower electrical conductivities than pure liquid Ga. The addition of In atoms is especially envisaged to reduce electrical conductivity due to a lower charge density at the indium atoms (see Figure 10b).…”
Section: Electrical and Thermal Transport Propertiesmentioning
confidence: 54%
See 1 more Smart Citation
“…204−206 The effect of the alloying element was related to the size mismatch, where alloying atoms with atom radii 15% or larger than the pure metal lead to a grave effect on the electrical conductivity, to a higher degree of disorder in the structure, and to weaker interatomic interactions. 78,204,206 A similar effect of alloying can be observed for the liquid metals EGaIn and Galinstan, which show lower electrical conductivities than pure liquid Ga. The addition of In atoms is especially envisaged to reduce electrical conductivity due to a lower charge density at the indium atoms (see Figure 10b).…”
Section: Electrical and Thermal Transport Propertiesmentioning
confidence: 54%
“…The liquid metal mercury shows a rather low electrical conductivity and the electrical conductivity is increased by alloying with most metals, such as In; both were attributed to a pseudopotential by Evans. , In contrast, by alloying, the electrical conductivity of other pure metals is typically lowered according to Mathiesson’s rule. The effect of the alloying element was related to the size mismatch, where alloying atoms with atom radii 15% or larger than the pure metal lead to a grave effect on the electrical conductivity, to a higher degree of disorder in the structure, and to weaker interatomic interactions. ,, A similar effect of alloying can be observed for the liquid metals EGaIn and Galinstan, which show lower electrical conductivities than pure liquid Ga. The addition of In atoms is especially envisaged to reduce electrical conductivity due to a lower charge density at the indium atoms (see Figure b) .…”
Section: Electrical and Thermal Transport Propertiesmentioning
confidence: 99%
“…Based on the results, it proves that the existence of impurities in the solder matrix will increase the electrical resistivity as follow the Matthiessen theory. 33 Comparison of current work with Nai et al 18 revealed that electrical resistivity of the SAC305-CNT solder joint is higher compared to the electrical resistivity of SAC305-CNT solder bulk. Different values of electrical resistivity by addition of CNT are mainly due to the form type of solder, types of CNT used, and the processing methods used.…”
Section: Resultsmentioning
confidence: 58%
“…When the amount reached a certain level, the passive film was broken down. The dissolution of Sn was accelerated by Cl − , which led to the formation of the complexes of SnCl − 3 and SnCl 2− 6 [32]. Thus, the corrosion current increased sharply.…”
Section: Analysis Of Electrochemical Corrosion Process Of Sn-07cu-xni...mentioning
confidence: 99%